2019
DOI: 10.21203/rs.2.15774/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparative study of Conventional methods and GeneXpert Mycobacterium tuberculosis Rifampicin (MTB/RIF) assay for diagnosis of childhood pulmonary tuberculosis

Abstract: Background Diagnosis of childhood TB (tuberculosis) is challenging because its symptoms resemble other diseases, very few (less than five) mycobacteria are capable of causing the disease and children do not or rarely expectorate. These peculiar attributes make childhood TB different from adult TB but it is still not being dealt differently from adult TB .Despite evidences from national, international data and WHO recommendation for use of Gene expert/TB/RIF assay, decision to start the treatment is based mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…However, in this study, the sensitivity, specificity, PPV, NPV, disease prevalence, and accuracy of the GeneXpert MTB/RIF assay for PTB were found to be 99.87%, 99.92%, 99.71%, 99.97%, 21.38%, and 99.91% respectively and for EPTB, the sensitivity, specificity, PPV, NPV, disease prevalence, and accuracy of the GeneXpert MTB/RIF assay counted for 99.45%, 99.84%, 98.70%, 99.93%, 10.64%, and 99.80%, respectively, compared to concentrated smear (Fluorescence Microscopy) method. Raina et al [29] reported that the sensitivity, specificity, PPV, and NPV of the GeneXpert MTB/RIF were 100%, 99.5%, 97.5%, and 100%, respectively, compared to the gold standard culture method.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the sensitivity, specificity, PPV, NPV, disease prevalence, and accuracy of the GeneXpert MTB/RIF assay for PTB were found to be 99.87%, 99.92%, 99.71%, 99.97%, 21.38%, and 99.91% respectively and for EPTB, the sensitivity, specificity, PPV, NPV, disease prevalence, and accuracy of the GeneXpert MTB/RIF assay counted for 99.45%, 99.84%, 98.70%, 99.93%, 10.64%, and 99.80%, respectively, compared to concentrated smear (Fluorescence Microscopy) method. Raina et al [29] reported that the sensitivity, specificity, PPV, and NPV of the GeneXpert MTB/RIF were 100%, 99.5%, 97.5%, and 100%, respectively, compared to the gold standard culture method.…”
Section: Discussionmentioning
confidence: 99%
“…Taking GeneXpert as the Gold standard, the sensitivity, and specificity of AFB smear assay were calculated by the following formula. 8 Sensitivity = True positive (TP)/True positive (TP) +False Negative (FN) X 100 Specificity= True Negative (TN)/True Negative+ False Positive (FP) X 100 Ethical Approval was taken from the Institutional Review Committee, Karnali Academy of Health Sciences "IRC-KAHS" (reference Number: 2078/2079/34). Valid and reliable data were collected at the laboratory of Karnali Academy of Health Sciences, Teaching Hospital Jumla.…”
Section: Methodsmentioning
confidence: 99%